A ceramic agglomerate abrasive particle, a ceramic agglomerate abrasive article, and a method of making
Patent Information
- Application Number
- CN202511260141.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-04
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2045-09-04
AI Technical Summary
但传统砂轮存在以下技术瓶颈:现有大颗粒砂轮的固有缺陷:1.天然大颗粒磨料粒度分布不均,导致磨削力波动和工件表面振纹;2.结合剂对大颗粒包裹不牢,高速重载下磨料脱落严重;3.磨粒钝化后缺乏自锐机制,磨削能耗急剧升高
1、本发明提供的陶瓷团聚磨料颗粒制备时可对其形状和粒径进行把控,确保得到的陶瓷团聚磨料颗粒形状和粒径相同或相似,保证陶瓷团聚磨料颗粒的一致性,并且CBN/GC混合磨料做为核层提供高硬度的切削刃,陶瓷结合剂包裹核层烧结后形成壳层,增强耐磨性。
Smart Images

Figure CN121179360B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of abrasive technology, specifically to a ceramic agglomerated abrasive particle, a ceramic agglomerated abrasive product, and a preparation method thereof. Background Technology
[0002] Grinding wheels, also known as bonded abrasives, are abrasive tools in which ordinary abrasive grains are bonded together with a bonding agent into a specific shape (mostly circular with a central through-hole) and possess a certain strength. Grinding wheels are the most important type of abrasive tool in grinding processes. With the gradual improvement of industrial manufacturing levels, the demand for large-mass grinding operations on heavy workpieces such as steel rolls and large casting blanks is increasing, placing higher demands on the cutting efficiency, chip removal capacity, and service life of grinding wheels. However, traditional grinding wheels have the following technical bottlenecks: the inherent defects of existing large-particle grinding wheels: 1. The uneven distribution of natural large-particle abrasive particles leads to fluctuations in grinding force and vibration marks on the workpiece surface; 2. The bonding agent does not firmly encapsulate the large particles, resulting in severe abrasive shedding under high speed and heavy load; 3. After the abrasive particles are passivated, there is a lack of self-sharpening mechanism, and the grinding energy consumption increases sharply. Summary of the Invention
[0003] In view of this, the present invention provides ceramic agglomerated abrasive particles, ceramic agglomerated abrasive products and preparation method, which controls the consistency of abrasive particles, maintains the stability of ceramic agglomerated abrasive products and realizes high-margin, high-efficiency cutting of ceramic agglomerated abrasive products.
[0004] To achieve the above objectives, the present invention provides ceramic agglomerated abrasive particles comprising the following raw materials in parts by weight: 27±3 parts CBN abrasive, 30±5 parts GC abrasive, 20±5 parts ceramic binder, 5±1 parts organic water-retaining agent, and 18±2 parts dispersant.
[0005] Optionally, the dispersant is a viscosity dispersant and a hydrophobic dispersant, wherein the viscosity dispersant is 16±1 parts and the hydrophobic dispersant is 2±1 parts.
[0006] Optionally, the viscosity dispersant includes one or more of fatty alcohol polyoxyethylene ether, maleic acid-acrylic acid copolymer, and polyurethane microparticles.
[0007] Optionally, the hydrophobic dispersant includes one or more of soybean lecithin, oleamide, and acrylic polymers.
[0008] Optionally, the organic water-retaining agent includes one or more of carboxymethyl cellulose, starch-acrylic acid copolymer, and sodium polyacrylate.
[0009] To achieve the above objectives, the present invention also provides a method for preparing ceramic agglomerated abrasive particles, characterized by comprising the following steps: S1. Mix CBN abrasive, GC abrasive, ceramic binder, and organic water-retaining agent evenly, and then stir them evenly with the dispersant in a mixing tank; then transfer the material to a mixing mixer and stir in a clockwise-counterclockwise-clockwise direction in sequence to obtain a semi-dry material; S2. Pour the semi-dry material into an injection molding machine and inject it into strips; dry the strips and crush them, then use a sieve to separate the ceramic agglomerate green body; after sintering and cooling, the ceramic agglomerate green body is used to obtain ceramic agglomerate abrasive particles.
[0010] Optionally, the clockwise-counterclockwise-clockwise mixing involves first using an E-shaped mixing head to mix clockwise for 300-400 revolutions in a mixing mixer, then using an E-shaped mixing head to mix counterclockwise for 30-40 revolutions, and finally using an E-shaped mixing head to mix clockwise for 4-8 minutes. Before each direction change, the material is shaped and kneaded into a ball before mixing.
[0011] Optionally, the diameter of the E-shaped stirring head for clockwise stirring is 2.5~3.5mm; the diameter of the E-shaped stirring head for counterclockwise stirring is 1~2mm.
[0012] Optionally, the sintering includes heating the ceramic agglomerate green material from room temperature to 600°C at a rate of 1-3°C / min, maintaining a pressure of 5-10 MPa, and holding the temperature for 30-60 min for degreasing and thorough degassing. Then, the temperature is increased to 1100°C at a rate of 5-10°C / min, and the pressure is linearly increased to 30±5 MPa to initially compact the powder. Then, the temperature is increased to 1250-1350°C at a rate of 1-3°C / min to achieve densification through particle rearrangement, and the temperature is held for 20-60 min to reach the final density.
[0013] To achieve the above objectives, the present invention also provides a ceramic agglomerate abrasive product comprising the following raw materials in weight percentage: 56.5-68.5% ceramic agglomerate abrasive particles as described in any one of claims 1-2, 7.5-9.5% resin liquid, 11-13% resin powder, 10-12% graphite balls, and 5-7% gypsum powder.
[0014] To achieve the above objectives, the present invention also provides a method for preparing ceramic agglomerated abrasive products, comprising the following steps: (1) The ceramic agglomerated abrasive particles are immersed in the resin liquid, stirred thoroughly, and resin powder is added and stirred continuously to obtain a semi-dry material; (2) Add gypsum powder to the semi-dry material and stir, then add graphite balls and stir to obtain a mixture; (3) The mixture is subjected to positive and negative pressure to obtain a green blank, which is dried, sintered, and then shaped to obtain a grinding wheel.
[0015] Optionally, the particle size of the ceramic agglomerated abrasive particles is 1.5~2mm; the stirring time of the gypsum powder is 30~50min; and the stirring time of the graphite balls is 25~45min.
[0016] Optionally, the drying and sintering process involves naturally drying the formed green body with sand for 3-5 hours, and then sintering it in a furnace along with the sand.
[0017] The above-described technical solution of the present invention has at least the following beneficial effects: 1. The ceramic agglomerate abrasive particles provided by this invention can control their shape and particle size during preparation, ensuring that the obtained ceramic agglomerate abrasive particles have the same or similar shape and particle size, thus ensuring the consistency of the ceramic agglomerate abrasive particles. Furthermore, the CBN / GC mixed abrasive serves as the core layer to provide a high-hardness cutting edge, and the ceramic binder encapsulates the core layer and forms a shell layer after sintering, enhancing wear resistance.
[0018] 2. In the ceramic agglomerate abrasive products provided by the present invention, the ceramic agglomerate abrasive particles combine with resin components to form a resin elastic network, which penetrates the ceramic gaps, imparts self-sharpening properties, absorbs impact loads, avoids particle breakage, and ensures stability under extreme working conditions. In addition, 300~500μm pores are naturally formed between the ceramic agglomerate abrasive particles, with a porosity of 35~45%, which improves the cooling and chip removal capacity, ensures continuous operation capability, and the graphite balls form a lubricating film on the inner wall of the pores, reducing chip adhesion and reducing grinding energy consumption. Attached Figure Description
[0019] Figure 1 The images show the structure of the grinding wheel prepared in the embodiments of the present invention, a schematic diagram of the microstructure of a part of the grinding wheel, and a schematic diagram of the microstructure of the ceramic agglomerated abrasive particles.
[0020] In the diagram: A represents the side structure of the grinding wheel; B represents the front structure of the grinding wheel; C represents a partial microstructure of the grinding wheel; C1 represents the ceramic agglomerated abrasive particles; C2 represents the resin and filler; D represents the microstructure of the ceramic agglomerated abrasive particles; D1 represents pores; D2 represents ceramic agglomerated abrasive particles; D3 represents the ceramic binder. Detailed Implementation
[0021] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the following will be described in conjunction with the accompanying drawings of the embodiments of the present invention. Figure 1 The technical solutions of the embodiments of the present invention will be clearly and completely described herein. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. All other embodiments obtained by those skilled in the art based on the described embodiments of the present invention are within the scope of protection of the present invention.
[0022] The types and types of raw materials used in the embodiments of this invention can be selected by those skilled in the art as needed. For clarity, the following types of raw materials are provided: Viscosity dispersants include one or more combinations of fatty alcohol polyoxyethylene ether, maleic acid-acrylic acid copolymer, and polyurethane microparticles; hydrophobic dispersants include one or more combinations of soybean lecithin, oleamide, and acrylic polymers; organic water-retaining agents include one or more combinations of carboxymethyl cellulose, starch-acrylic acid copolymer, and sodium polyacrylate. Example 1 This invention provides ceramic agglomerated abrasive particles, comprising the following raw materials in parts by weight: 27 parts CBN abrasive, 30 parts GC abrasive, 20 parts ceramic binder, 5 parts organic water-retaining agent, 16 parts viscosity dispersant, and 2 parts hydrophobic dispersant.
[0023] The preparation method of ceramic agglomerated abrasive particles includes the following steps: Mixing: Mix the weighed CBN abrasive, GC abrasive, ceramic binder, and organic water-retaining agent evenly, then mix with the dispersant in a mixing tank using a horn for 5 minutes until uniformly stirred; transfer the uniformly stirred material to a mixing mixer and first stir clockwise 350 times with a 3mm E-shaped stirring head, then stir counterclockwise 35 times with a 1.5mm E-shaped stirring head, and finally stir clockwise for 6 minutes with a 3mm E-shaped stirring head; before each change of direction, knead the material into a ball and then stir to obtain a semi-dry material.
[0024] Physical granulation: Semi-dry material is poured into an injection molding machine, the injection pressure is set to 28MPa, and the required injection tube is installed according to the desired particle size to inject it into strips. After drying the strips, they are crushed and sieved using a sieve with a particle size one size larger than the desired size to obtain ceramic agglomerate green body. The ceramic agglomerate green body is sintered and cooled to obtain ceramic agglomerate abrasive particles. Sintering includes heating the ceramic agglomerate green body from room temperature to 600℃ at a rate of 2℃ / min, maintaining a pressure of 8MPa, and holding the temperature for 50 minutes to degrease and fully degas, achieving safe removal of organic matter. The slow heating allows the water-retaining agent and dispersant to slowly decompose and vaporize, avoiding cracking and blistering of the green body. Vacuum or inert gas protection is required. Maintaining the temperature ensures full degassing and complete removal of organic matter decomposition products. Complete removal of organic matter ensures uniform system temperature. Then, the temperature is increased to 1100℃ at 8℃ / min, with the pressure linearly increased to 30±5MPa. At this point, organic matter has been completely removed, allowing for a faster heating rate. The simultaneous increase in pressure and temperature initially densifies the powder. Next, the temperature is increased to 1300℃ at 2℃ / min, representing the core sintering stage, approaching the eutectic temperature. A liquid phase is generated, and slow heating ensures uniform distribution of the liquid phase, effectively wetting the CBN particles. Densification is achieved through particle rearrangement. The temperature is maintained for 40 minutes, marking the final sintering stage. A dissolution-precipitation mechanism further eliminates porosity, achieving the final density. Cooling is performed in-furnace, with slow cooling to release thermal stress, prevent product cracking, and allow the binder phase to fully crystallize. After cooling, ceramic agglomerates of 1.5~2mm are screened out.
[0025] Example 2 This invention provides ceramic agglomerated abrasive particles, comprising the following raw materials in parts by weight: 24 parts CBN abrasive, 25 parts GC abrasive, 25 parts ceramic binder, 6 parts organic water-retaining agent, 17 parts viscosity dispersant, and 3 parts hydrophobic dispersant.
[0026] The preparation method of ceramic agglomerated abrasive particles includes the following steps: Mixing: Mix the weighed CBN abrasive, GC abrasive, ceramic binder, and organic water-retaining agent evenly, then mix with the dispersant in a mixing tank using a horn tool for 5 minutes until uniformly stirred; transfer the uniformly stirred material to a mixing mixer and first stir clockwise 300 times with a 3.5mm E-shaped stirring head, then stir counterclockwise 40 times with a 1mm E-shaped stirring head, and finally stir clockwise for 4 minutes with a 3.5mm E-shaped stirring head; before each change of direction, knead the material into a ball and then stir to obtain a semi-dry material.
[0027] Physical granulation: Semi-dry material is poured into an injection molding machine, the injection pressure is set to 30MPa, and the required injection tube is installed according to the desired particle size to inject it into strips. After drying the strips, they are crushed and sieved using a sieve with a particle size one size larger than the desired size to obtain ceramic agglomerate green body. The ceramic agglomerate green body is sintered and cooled to obtain ceramic agglomerate abrasive particles. Sintering includes heating the ceramic agglomerate green body from room temperature to 600℃ at a rate of 3℃ / min, maintaining a pressure of 5MPa, and holding the temperature for 60 minutes for degreasing and thorough degassing to safely remove organic matter. The slow heating allows the water-retaining agent and dispersant to slowly decompose and vaporize, preventing cracking and blistering of the green body. Vacuum or inert gas protection is required. Maintaining the temperature ensures thorough degassing and the removal of organic decomposition products. Complete removal of organic matter ensures uniform system temperature. Then, the temperature is increased to 1100℃ at 5℃ / min, with the pressure linearly increased to 25MPa. At this point, organic matter has been completely removed, allowing for a faster heating rate. The simultaneous increase in pressure and temperature initially densifies the powder. Next, the temperature is increased to 1350℃ at 3℃ / min, representing the core sintering stage, approaching the eutectic temperature. A liquid phase is generated, and slow heating ensures uniform distribution of the liquid phase, effectively wetting the CBN particles and achieving densification through particle rearrangement. The temperature is maintained for 20 minutes, marking the final sintering stage. A dissolution-precipitation mechanism further eliminates porosity, achieving the final density. Cooling is performed in-furnace, with slow cooling to release thermal stress, prevent product cracking, and allow the binder phase to fully crystallize. After cooling, ceramic agglomerate abrasive particles of the desired size are screened out.
[0028] Example 3 This invention provides ceramic agglomerated abrasive particles, comprising the following raw materials in parts by weight: 30 parts CBN abrasive, 35 parts GC abrasive, 15 parts ceramic binder, 4 parts organic water-retaining agent, 15 parts viscosity dispersant, and 1 part hydrophobic dispersant.
[0029] The preparation method of ceramic agglomerated abrasive particles includes the following steps: Mixing: Mix the weighed CBN abrasive, GC abrasive, ceramic binder, and organic water-retaining agent evenly, then mix with the dispersant in a mixing tank using a horn mixer for 5 minutes until uniformly stirred; transfer the uniformly stirred material to a mixing mixer and first stir clockwise 400 times with a 2.5mm E-shaped stirring head, then stir counterclockwise 30 times with a 2mm E-shaped stirring head, and finally stir clockwise for 8 minutes with a 2.5mm E-shaped stirring head; before each change of direction, knead the material into a ball and then stir to obtain a semi-dry material.
[0030] Physical granulation: Semi-dry material is poured into an injection molding machine, the injection pressure is set to 29 MPa, and the required injection tube is installed according to the desired particle size to inject it into strips. The strips are dried and then pulverized. The ceramic agglomerate green body is then sieved using a sieve one particle size larger than the desired size. The ceramic agglomerate green body is sintered and cooled to obtain ceramic agglomerate abrasive particles. Sintering involves heating the ceramic agglomerate green body from room temperature to 600°C at a rate of 1°C / min, maintaining a pressure of 10 MPa, and holding the temperature for 30 minutes to degrease and fully degas, safely removing organic matter. Slow heating allows the water-retaining agent and dispersant to decompose and vaporize slowly, preventing cracking and blistering of the green body. Vacuum or inert gas protection is required. Maintaining the temperature ensures sufficient degassing and removal of organic decomposition products. Complete removal of organic matter ensures uniform system temperature. Then, the temperature is increased to 1100℃ at 10℃ / min, with the pressure linearly increased to 35MPa. At this point, organic matter is completely removed, allowing for a faster heating rate. The simultaneous increase in pressure and temperature initially densifies the powder. Next, the temperature is increased to 1250℃ at 1℃ / min, representing the core sintering stage, approaching the eutectic temperature. A liquid phase is generated, and slow heating ensures uniform distribution of the liquid phase, effectively wetting the CBN particles and achieving densification through particle rearrangement. The temperature is maintained for 60 minutes, marking the final sintering stage. A dissolution-precipitation mechanism further eliminates porosity, achieving the final density. Cooling is performed in-furnace, with slow cooling to release thermal stress, prevent product cracking, and allow the binder phase to fully crystallize. After cooling, ceramic agglomerates of 1.5~2mm are screened out.
[0031] Example 4 The present invention provides a ceramic agglomerate abrasive product comprising the following raw materials by weight percentage: 62.5% ceramic agglomerate abrasive particles, 8.5% resin liquid, 12% resin powder, 11% graphite balls, and 6% gypsum powder.
[0032] The preparation method of ceramic agglomerated abrasive products includes the following steps: Weigh the raw materials according to the above weight percentages and set aside. Immerse the ceramic agglomerated abrasive particles in the resin liquid and stir thoroughly. The particle size of the ceramic agglomerated abrasive particles is 1.5 mm. Add resin powder and continue stirring to obtain a semi-dry material. Add gypsum powder and stir for 30 minutes at a stirring speed of 60 rpm. Then add graphite balls and stir for 25 minutes at a stirring speed of 45 rpm to obtain a mixture. After the mixture is subjected to positive and negative pressure, a green body is formed. It is buried in sand and dried naturally for 4 hours. Then it is sintered in the furnace with the sand. After sintering, diamond grinding wheels are used to process and modify the shape according to the required shape and size of the grinding wheel to obtain the grinding wheel.
[0033] Example 5 This invention provides a ceramic agglomerate abrasive product comprising the following raw materials by weight percentage: 58.5% ceramic agglomerate abrasive particles, 9.5% resin liquid, 13% resin powder, 12% graphite balls, and 7% gypsum powder.
[0034] The preparation method of ceramic agglomerated abrasive products includes the following steps: Weigh the raw materials according to the above weight percentages and set aside. Immerse the ceramic agglomerated abrasive particles in the resin liquid and stir thoroughly. The particle size of the ceramic agglomerated abrasive particles is 2 mm. Add resin powder and continue stirring to obtain a semi-dry material. Add gypsum powder and stir for 40 minutes at a stirring speed of 50 rpm. Then add graphite balls and stir for 35 minutes at a stirring speed of 60 rpm to obtain a mixture. After the mixture is subjected to positive and negative pressure, a green body is formed. It is buried in sand and naturally dried for 3 hours. Then it is sintered in the furnace with the sand. After sintering, a diamond grinding wheel is used to process and modify the shape according to the required grinding wheel shape and size to obtain the grinding wheel.
[0035] Example 6 This invention provides a ceramic agglomerate abrasive product comprising the following raw materials by weight percentage: 66.5% ceramic agglomerate abrasive particles, 7.5% resin liquid, 11% resin powder, 10% graphite balls, and 5% gypsum powder.
[0036] The preparation method of ceramic agglomerated abrasive products includes the following steps: Weigh the raw materials according to the above weight percentages and set aside. Immerse the ceramic agglomerated abrasive particles in the resin liquid and stir thoroughly. The particle size of the ceramic agglomerated abrasive particles is 1.8 mm. Add resin powder and continue stirring to obtain a semi-dry material. Add gypsum powder and stir for 50 minutes at a stirring speed of 30 rpm. Then add graphite balls and stir for 45 minutes at a stirring speed of 25 rpm to obtain a mixture. After the mixture is subjected to positive and negative pressure, a green body is formed. It is buried in sand and naturally dried for 5 hours. Then it is sintered in the furnace with the sand. After sintering, diamond grinding wheels are used to process and modify the shape according to the required shape and size of the grinding wheel to obtain the grinding wheel.
[0037] Comparative Example 1 Compared to Example 1, the only difference is that the materials are continuously stirred clockwise while being transferred to the mixer. All other steps and operations are the same as in Example 1.
[0038] Comparative Example 2 Compared to Example 1, the only difference is that a traditional granulation method is used during granulation, i.e., the semi-dry material is mixed with plasticizer instead of being injected into strips. All other steps and operations are the same as in Example 1.
[0039] Comparative Example 3 Compared to Example 4, the only difference is that resin liquid is used exclusively, and resin powder is not used. All other steps and operations are the same as in Example 4.
[0040] Comparative Example 4 Compared with Example 4, the only difference is that the stirring time for the gypsum powder is 60 minutes and the stirring time for the graphite balls is 50 minutes. All other steps and operations are the same as in Example 4.
[0041] The performance of the abrasive particles prepared in Examples 1-2 and Comparative Examples 1-2 was tested, and the results are shown in Table 1.
[0042] Table 1. Performance of abrasive particles prepared in Examples 1-2 and Comparative Examples 1-2
[0043] Note: TI is a fixed number of impacts method. The sample is impacted a certain number of times and then sieved. The percentage of material remaining on the sieve (unbroken material) indicates the level of impact toughness. The value is the TI value. A high TI value reflects, to a certain extent, the strong uniformity of abrasive particles.
[0044] As shown in Table 1, the abrasive particles prepared in the embodiments of the present invention have significantly better hardness and impact toughness than those in the comparative example.
[0045] The performance of the grinding wheels prepared in Examples 3-4 and Comparative Examples 3-4 was tested, and the results are shown in Table 2.
[0046] Table 2. Performance of grinding wheels prepared in Examples 3-4 and Comparative Examples 3-4
[0047] Note: The hardness of grinding wheels is divided into several grades, such as A~G, H, J, K, L, M, N, P, Q, R, S, T and Y, with A being the lowest and Y being the highest.
[0048] As shown in Table 2, the grinding wheel prepared in the embodiments of the present invention has significantly better overall performance in terms of hardness, wear resistance, and porosity than the comparative example.
[0049] The structural diagram of the grinding wheel prepared in this embodiment of the invention, the schematic diagram of the microstructure of a portion of the grinding wheel, and the schematic diagram of the microstructure of the ceramic agglomerated abrasive particles are shown below. Figure 1 .
[0050] The above are preferred embodiments of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A ceramic agglomerated abrasive particle, characterized in that, The raw materials include the following parts by weight: 27±3 parts CBN abrasive, 30±5 parts GC abrasive, 20±5 parts ceramic binder, 5±1 parts organic water-retaining agent, and 18±2 parts dispersant; the dispersant is a viscosity dispersant and a hydrophobic dispersant, wherein the viscosity dispersant is 16±1 parts and the hydrophobic dispersant is 2±1 parts; the viscosity dispersant includes one or more combinations of fatty alcohol polyoxyethylene ether, maleic acid-acrylic acid copolymer, and polyurethane microparticles; the hydrophobic dispersant includes one or more combinations of soybean lecithin, oleamide, and acrylic polymer.
2. A method for preparing ceramic agglomerated abrasive particles as described in claim 1, characterized in that, Includes the following steps: S1. Mix CBN abrasive, GC abrasive, ceramic binder, and organic water-retaining agent evenly, and then stir them evenly with the dispersant in a mixing tank; then transfer the material to a mixing mixer and stir in a clockwise-counterclockwise-clockwise direction in sequence to obtain a semi-dry material; S2. Pour the semi-dry material into an injection molding machine and inject it into strips; dry the strips and crush them, then use a sieve to separate the ceramic agglomerate green body; after sintering and cooling, the ceramic agglomerate green body is used to obtain ceramic agglomerate abrasive particles.
3. The method for preparing ceramic agglomerated abrasive particles according to claim 2, characterized in that, The clockwise-counterclockwise-clockwise mixing process involves first using an E-shaped mixing head to mix clockwise for 300-400 revolutions in the mixer, then using an E-shaped mixing head to mix counterclockwise for 30-40 revolutions, and finally using an E-shaped mixing head to mix clockwise for 4-8 minutes. Before each direction change, the material is shaped and kneaded into a ball before mixing.
4. The method for preparing ceramic agglomerated abrasive particles according to claim 3, characterized in that, The diameter of the E-shaped stirring head for clockwise stirring is 2.5~3.5mm; the diameter of the E-shaped stirring head for counterclockwise stirring is 1~2mm.
5. The method for preparing ceramic agglomerated abrasive particles according to claim 2, characterized in that, The sintering process involves heating the ceramic agglomerate green material from room temperature to 600°C at a rate of 1-3°C / min, maintaining a pressure of 5-10 MPa, and holding the temperature for 30-60 min to degrease and fully degas the material. Then, the temperature is increased to 1100°C at a rate of 5-10°C / min, and the pressure is linearly increased to 30±5 MPa to initially compact the powder. Finally, the temperature is increased to 1250-1350°C at a rate of 1-3°C / min to achieve densification through particle rearrangement, and the temperature is held for 20-60 min to reach the final density.
6. A ceramic agglomerated abrasive product, characterized in that, The raw materials include the following weight percentages: 56.5-68.5% ceramic agglomerated abrasive particles as described in claim 1, 7.5-9.5% resin liquid, 11-13% resin powder, 10-12% graphite balls, and 5-7% gypsum powder.
7. A method for preparing a ceramic agglomerated abrasive product as described in claim 6, characterized in that, Includes the following steps: (1) The ceramic agglomerated abrasive particles are immersed in the resin liquid, stirred thoroughly, and resin powder is added and stirred continuously to obtain a semi-dry material; (2) Add gypsum powder to the semi-dry material and stir, then add graphite balls and stir to obtain a mixture; (3) The mixture is subjected to positive and negative pressure to obtain a green blank, which is dried, sintered, and then shaped to obtain a grinding wheel.
8. A method for preparing a ceramic agglomerated abrasive product as described in claim 7, characterized in that, The ceramic agglomerated abrasive particles have a particle size of 1.5~2mm; the gypsum powder is stirred for 30~50min, and the graphite balls are stirred for 25~45min.
9. A method for preparing a ceramic agglomerated abrasive product as described in claim 7, characterized in that, The drying and sintering process involves burying the formed green body in sand and letting it dry naturally for 3-5 hours, then sintering it in a furnace along with the sand.
Citation Information
Patent Citations
Grinding pad for gallium oxide single crystals and preparation method of grinding pad
CN106272035A
Composite cluster abrasive material and preparation method thereof
CN115746788A